Axilla; a rare variation: axillary arch muscle - Nikam, Vasudha Ravindra; Patil, Priya Santosh; Patil, Ashalata Deepak; Pote, Aanand Jagnnath; Gune, Anita Rahul (International Journal of Research in Medical Sciences, 2017)
Axillary arch muscle or the Langer’s muscle is one of the rare muscular variation in the axillary region. It is the additional muscle slip extending from latissimus dorsi in the posterior fold of axilla to the pectoralis major or other neighbouring muscles and bones. In the present article a case of 68 yrs old female cadaver with axillary arch in the left axillary region is reported. It originated from the anterior border of lattissimus dorsi and merged with the short head of biceps and pectoralis major muscles. The arch was compressing the axillary vein as well as the branches of the cords of brachial plexus. The presence of the muscle has important clinical implications, as the position, unilateral presence, axillary vein entrapment, multiple insertions makes the case most complicated. Recognising the presence of axillary arch muscle in such complex form is important in clinical practice as the arch causes the difficulties in staging lymph nodes, axillary surgery, thoracic outlet syndrome, shoulder instability or cosmetic problems. The anatomy, embryological and clinical importance of this muscular variation is discussed in this paper.